2015
DOI: 10.1111/acel.12259
|View full text |Cite
|
Sign up to set email alerts
|

In vitro caloric restriction induces protective genes and functional rejuvenation in senescent SAMP8 astrocytes

Abstract: Astrocytes are key cells in brain aging, helping neurons to undertake healthy aging or otherwise letting them enter into a spiral of neurodegeneration. We aimed to characterize astrocytes cultured from senescence-accelerated prone 8 (SAMP8) mice, a mouse model of brain pathological aging, along with the effects of caloric restriction, the most effective rejuvenating treatment known so far. Analysis of the transcriptomic profiles of SAMP8 astrocytes cultured in control conditions and treated with caloric restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…SAMP8 microglia generally showed the amoeboid morphology that is associated with an activated state ( Aldana, 2019 ). However, SAMP8 astrocytes did not show overt reactive phenotype in control conditions, although they have shown some functional deficiencies in vitro ( García-Matas et al, 2008 , 2015 ). Experiments in cell cultures have shown that both microglia and astrocytes are able to synthesize IL1β, IL6 and TNFα ( Lam et al, 2017 ; Rodgers et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAMP8 microglia generally showed the amoeboid morphology that is associated with an activated state ( Aldana, 2019 ). However, SAMP8 astrocytes did not show overt reactive phenotype in control conditions, although they have shown some functional deficiencies in vitro ( García-Matas et al, 2008 , 2015 ). Experiments in cell cultures have shown that both microglia and astrocytes are able to synthesize IL1β, IL6 and TNFα ( Lam et al, 2017 ; Rodgers et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes and microglia cultured from neonatal SAMP8 neocortex show senescent and pathological traits that might greatly contribute to pathological brain aging in these mice ( García-Matas et al, 2008 , 2015 ; Díez-Vives et al, 2009 ). Here we used mixed glial cultures enriched in astrocytes and almost pure microglia cultures to discern inflammation mechanisms at the cellular level.…”
Section: Methodsmentioning
confidence: 99%
“…An increase of oxidative stress in the brain is a hallmark of aging as well as neurodegenerative diseases. It is evident that DR reduces oxidative stress in senescent astrocytes as well as in aged brains, as evidenced by reduction in ROS and protein oxidation [16,151,152,153,154]. Although how DR reduces oxidative stress in the brain remains elusive, several potential mechanisms of DR’s antioxidative functions have been proposed [155].…”
Section: A Potential Mechanistic Link Between Dietary Restriction mentioning
confidence: 99%
“… 15 , 18 , 19 , 22 The increase in senescent cells that accompanies the aging process is a consequence of damaged DNA accumulation along life because of telomere shortening, genotoxic stress and diet. 22 , 23 , 24 , 25 , 26 , 27 , 28 The mammalian transcription factors FOXO (forkhead box O transcription factor) and their orthologs in C. elegans and D. melanogaster are associated with longevity. 29 It is required for the normal response to oxidative stress and is negatively regulated by AKT phosphorylation that can be activated by insulin/insulin-like growth factor (IGF).…”
mentioning
confidence: 99%